2014
DOI: 10.1051/0004-6361/201322180
|View full text |Cite
|
Sign up to set email alerts
|

Non-LTE spectral analysis of the AM CVn system PTF 09hpk during quiescence

Abstract: Context. AM Canum Venaticorum stars are close, interacting binary systems with a white dwarf primary surrounded by a heliumdominated accretion disk. Because of the short orbital periods, the unseen secondary must be compact, too. Different evolutionary scenarios for the formation of these systems resulting in different kinds of secondaries are possible. Aims. Quantitative spectral analyses of accretion-disk spectra can reveal the nature of the secondary. We investigate a particular AM CVn system, discovered re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…None of the systems show a halo orbit. In a small number of AM CVn stars, the extreme depletion of heavy elements have been taken as evidence that these stars were halo objects (GP Com: Marsh et al (1991); V396 Hya: Nagel et al (2009) and PTF1 J0719+4858: Gehron et al (2014). Our study has shown that these AM CVn stars are likely thin or thick disk objects and not halo objects.…”
Section: Galactic Distributionmentioning
confidence: 55%
“…None of the systems show a halo orbit. In a small number of AM CVn stars, the extreme depletion of heavy elements have been taken as evidence that these stars were halo objects (GP Com: Marsh et al (1991); V396 Hya: Nagel et al (2009) and PTF1 J0719+4858: Gehron et al (2014). Our study has shown that these AM CVn stars are likely thin or thick disk objects and not halo objects.…”
Section: Galactic Distributionmentioning
confidence: 55%
“…Radial velocity measurements show that these lines originate from the white dwarf (Marsh 1999;Roelofs et al 2005;Kupfer et al 2015) and is likely boundary layer emission from the surface of the white dwarf (e.g. Green et al 2019a;Gehron et al 2014).…”
Section: The Average Spectra and Spectral Linesmentioning
confidence: 99%
“…In the latter case a red-giant like extended envelope forms and components, most probably, merge 1 . Thus, the existing interacting double-degenerates should start their evolution with Ṁ∼ 10 −6 M⊙ yr −1 and may evolve in a Hubble time to Ṁ∼ 10 −12 M⊙ yr −1 as it is theoretically inferred (Tutukov & Yungelson 1979;Nelemans et al 2001;Deloye et al 2007) and supported by the analysis of the spectra of several AM CVn stars (Krausz et al 2010;Gehron et al 2014).…”
Section: Introductionmentioning
confidence: 74%